Intraoperative liver ultrasound - Gastambide, Carmelo; Cohen, Henry; Olivera, Eduardo; Ribero, G; Rodríguez, O. (Cirugía del Uruguay, 1991)
The author presents a descriptive paper in which he compares images of intraoperative hepatic echography obtained with a 8-mode echography, with those studied in !aeta/ and adult cadaveric livers, injected with e/astomerica coloured material. The author comes to the conclusion that the method reproduces with great fidelity the normal anatomica/ disposition, beside making possible the determination of the eventual/y abnormal ones.